Cystatin C-based CKD-EPI estimated glomerular filtration rate equations as a better strategy for mortality stratification in acute heart failure: A STROBE-compliant prospective observational study. Issue 44 (30th October 2020) - Cheang, Iokfai; Liao, Shengen; Yao, Wenming; Lu, Xinyi; Gao, Rongrong; Zhou, Yanli; Zhang, Haifeng; Li, Xinli
Abstract : Abstract: An increasing number of studies outline renal function as an important risk marker for mortality in acute heart failure (AHF). However, routine estimation of glomerular filtration rate (eGFR) based on serum creatinine is imprecise. This study aims to compare the prognostic impact of CKD-EPI creatinine based equation (eGFRcr), cystatin C based equation (eGFRcyst), and creatinine–cystatin C equation (eGFRcrcyst) for the mortality stratification in AHF. A total of 354 Patients with AHF were prospectively included between January 2012 and June 2016. Creatinine and cystatin C were measured using the same blood sample tube on admission. We quantified eGFR by the eGFRcr, eGFRcyst, and eGFRcrcyst equations. The continuous net reclassification improvement (cNRI) and integrated discrimination improvement (IDI) were calculated to compare the discriminative prognostic value of different CKD-EPI formula. After a median follow-up of 35 months, 161 patients (45.5%) died. Reduced eGFRcyst and eGFRcrcyst remained significant association with death after adjustment. eGFRcyst showed the best area under the curve value (0.706) for the prediction of all-cause mortality. Considering mortality reclassification, both eGFRcyst (IDI = 7.3%, P < .001; cNRI = 19.6%, P = .012) and eGFRcrcyst (IDI = 4.3%, P < .001; cNRI = 8.7%, P = .138) showed its tendency in improving risk prediction compared to eGFRcr. Compared to eGFRcrcyst showed, eGFRcyst further improved mortality stratification (IDI = 3%, P = .049; cNRI = 11.1%, P = .036). In patients with AHF, our study demonstrates the eGFR calculated by CKD-EPI cystatin C-based equation improved the risk stratification of mortality over both creatinine-based and creatinine/cystatin C-based equations. Abstract : Supplemental Digital Content is available in the text